Levels of Anxiety and Depression Before Palliative Reirradiation Are Comparable to Those Before First Palliative Radiotherapy - Nieder, Carsten (Cureus, 2018)
Introduction: The purpose of this study was to evaluate whether or not patients scheduled for the reirradiation of a previously treated target volume report reduced levels of anxiety and depression, compared to patients receiving their first course of palliative radiotherapy, e.g., because they are familiar with the process of treatment planning and delivery. Methods: A retrospective comparison of two groups of patients (37% reirradiated, overall 102 patients), which scored their symptoms before palliative radiotherapy with the Edmonton symptom assessment system (ESAS). Results: The two groups differed significantly with regard to the incidence of bone metastases, which was higher in the reirradiation group. Mean anxiety and depression scores were not significantly different between the two groups. The same was true for the proportion of patients with symptom scores ≥4. Analyses limited to patients treated for bone metastases revealed no significant differences either. Survival was similar, too. Conclusion: The facts that similar ESAS scores of anxiety and depression were observed and that prognosis was comparable suggest that the magnitude of these symptoms might be associated with the presence of incurable cancer itself (or the related somatic symptom burden) rather than the setting in which palliative radiotherapy is performed.